Haiti : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criterion, Modification of Performance Criteria, and Extension of the Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Haiti. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the Fifth Review for Haiti under the Poverty Reduction and Growth Facility. The program seeks to protect critical spending for infrastructure rehabilitation and poverty reduction strategy paper implementation in light of significant revenue shortfalls, thus maintaining growth and reducing the impact of the global crisis on the population. All end-March quantitative criteria, structural benchmarks, and all but one structural performance criteria were met. The latter was implemented with a small delay. IMF staff supports the authorities' request for a waiver and recommends completion of the review.